Analysis of some selections in the basic textbooks in reading in grade four in the public elementary schools - Achanzar, Rizalina (Hernando) 1927- (1967)
The aim of the study is to analyze the exercises in the Study Helps of 15 stories randomly chosen from the Grade Four textbooks in Reading, namely, Story Parade, Level I and More Stories on Parade, Level II in relation to the skills they develop in the different dimensions, and to propose exercises for their enrichment. The study shows whether the Study Helps of certain stories in the Grade Four basic readers develop the desired reading skills. Further, the paper furnishes exercises designed to enrich the Study Helps in areas that the Study Helps do not adequately provide for the development of other reading skills.
Thesis (M.A.T. Reading)--University of the Philippines, Diliman.
Keywords: Reading (Elementary).